Selection and role of a mix rosemary (Rosmarinus officinalis) - palmitate ascorbyl as antioxidant in a frying process - PEÑALOZA, Jeanine Kathleen; ROJANO, Benjamin Alberto; PIEDRAHITA, Ana María (Vitae, 2017)
Background: Several studies have found that rosemary has active components with antioxidant potential, and that is why, an extract combined with ascorbyl palmitate provides protection for systems with high fat content was obtained. Aims: The aim of this study was to evaluate the effect of the addition of two extracts of rosemary (Rosmarinus officinalis): AP10R and AP30R at three concentrations 1000, 1500 and 2000ppm, on the oxidative stability of palm oil subjected to accelerated oxidation and frying conditions, Methods: controlling the concentration of hydroperoxides, total polar compounds and the thermal stability of phenolic compounds it is conducted in the oil through fluorescence spectroscopy and were evaluated with and without addition of the extract. Results: The extract AP10R to 2000ppm inhibited the oxidation of olein in 30.38% and 60.84% in terms of the concentration of total polar compounds and hydroperoxides, respectively. In addition, Conclusions: Results indicated that heating decreases the concentration of polyphenols; this decrease was most evident in the olein without extract, reflecting the effect of rosemary extract on the stability of used oil polyphenols.